Hubungan Kualitas Tidur Remaja Selama Pandemi Covid-19 dengan Aktivitas Fisik Serta Screen-Time - Arwan Bin Laeto; Siti Sarahdeaz Fazzaura Putri; Eka Febri Zulissetiana; Swanny (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Abstract. Public health is an aspect that has shown a decline sincethe COVID-19 pandemic emerged, both globally and in Indonesia.Seeing these conditions, the Indonesian government has implemented restrictions on community mobility, including the learning process (lectures) which must be held online. This triggers an increasein screen time among teenagers, while at the same time there is adecrease in sleep quality and low physical activity. The purpose ofthis study was to determine the relationship between sleep qualityduring the COVID-19 pandemic with the level of physical activity andthe degree of screen time for adolescents. The objection of thisresearch is to analyze the relationship between adolescent sleepquality during the Covid-19 pandemic with levels of physical activityand screen-time. Methods: The study used an observationalapproach with a crosssectional design of 185 students. The researchwas conducted in November 2021 at the Faculty of Medicine,Sriwijaya University. Research data collection through onlinequestionnaires and data analysis using Chi square test. Results: Thisstudy shows the results, as many as 77.82% of students have poorsleep quality, 48.64% have low levels of physical activity and 76.22%of students show high smartphone screen-time. The bivariate testshowed that there was a significant relationship between the levelof physical activity and sleep quality, namely p = 0.002. However,there was no significant relationship between sleep quality and thedegree of screen-time (p = 0.253). Conclusion: The level of physicalactivity has a significant relationship with adolescent sleep quality.Physical activity is a factor that affects teenagers in getting goodquality sleep during the COVID-19 pandemic.